Preparation of multiparticulate systems for oral delivery of a micronized or nanosized poorly soluble drug. (1st September 2016) - Cerea, Matteo; Pattarino, Franco; Foglio Bonda, Andrea; Palugan, Luca; Segale, Lorena; Vecchio, Carlo
Abstract: The purpose of the present work was to prepare multiparticulate drug delivery systems for oral administration of a poorly soluble drug such as itraconazole. Multiparticulate systems were prepared by extrusion/spheronization technique using a mix of crospovidone, low viscosity hypromellose, microcrystalline cellulose, micronized drug and water. In order to improve the release performance of the multiparticulate systems, the micronized drug was suspended in water with polysorbate 20 and nanonized by a high-pressure homogenization. The suspension of drug nanoparticles was then spray-dried for enabling an easy handling of the drug and for preventing the over-wetting of the powders during extrusion/spheronization processing. Both multiparticulate units prepared with micronized or nanonized drug showed acceptable disintegrating properties. The nanosizing of micronized drug powder provided a significant improvement of drug dissolution rates of the multiparticulates.